Evaluating radiation safety knowledge and practices in dental professionals: findings from a cross-sectional survey - Mohammad Aljamal; Tala Batakat; Zuhal Hamd; Mohamed Abuzaid; Awadia Gareeballah (BMC Medical Education)
Abstract Background Dental radiography is used extensively for diagnosing dental and maxillofacial disorders. Therefore, dental professionals must have adequate knowledge of and practice related to radiation protection and safety. The main objective of this study was to determine the degree of radiation safety knowledge among dental professionals and students in Palestine’s northwest West Bank. Methodology A cross-sectional study was conducted to evaluate radiation safety knowledge and practices among dental professionals in the West Bank, Palestine, from February to September 2023. Seven hundred fifteen participants (103 dentists and 612 dental students) completed a questionnaire with demographic information and eighteen closed-ended questions. The data were analyzed via SPSS version 27 and DATAtab, and chi-square and nonparametric tests were used to assess the relationships between variables. Results A low overall knowledge level was noted (average score of 7.51 ± 2.67 out of 16). The students had a significantly higher mean rank in knowledge and practice than did the dentists (368.44 vs. 295.98, p = 0.001). Among the students, the mean ranks were higher in the 4th and 5th academic years than in the 2nd and 3rd academic years. In contrast, there were insignificant differences in the scores of knowledge and practice among dentists with different experience levels; those with more than 14 years and 5–9 years of experience had higher mean ranks than did the other dentists. Conclusion There was a lack of knowledge and practice regarding radiation protection and safety among the respondents. Students demonstrated higher knowledge scores than dentists, despite having less clinical experience, possibly due to more recent exposure to formal training in radiation protection. While there are no significant differences in knowledge among dentists of varying experience, more experienced dentists generally rank higher. To address this, raising awareness of radiation safety among dental professionals through improved curricula and ongoing training is essential. Awareness campaigns should also emphasize the importance of radiation safety for professionals and patients.